Biochar impact on soil health and tree-based crops: a review - Joao A. Antonangelo; Xiao Sun; Humberto de Jesus Eufrade-Junior (Biochar)
Abstract Biochar produced from pyrolysis of biomass such as wood, canopy, animal manure, and agricultural waste is recognized for its stability and for being a benefactor of soil health and plant growth. Its application in forestry is an area with growing research interest due to its ability to enhance soil physicochemical properties, including structure, water retention, and nutrient availability, thereby boosting plant growth, drought tolerance, and resistance to pests and diseases. However, the effectiveness of biochar varies based on factors like biochar type, application rate, soil type, and tree species. Potential risks associated with biochar use include nutrient immobilization, increased pH in alkaline soils, and enhanced leaching of toxic elements. Despite its promise, challenges such as knowledge gaps, lack of site-specific studies, and concerns of economic viability hinder widespread adoption of biochar in forestry. This qualitative review compiles over 150 published works from the past two decades on biochar application in forestry. It assesses the impacts of biochar on soil health and tree crops, highlighting its potential to improve soil fertility and promote tree growth. The review identifies significant findings, such as the positive influence of biochar on soil and plant health and outlines existing knowledge gaps that need addressing. By synthesizing current research, the review proposes future directions to optimize biochar use in sustainable forestry management, emphasizing the need for tailored approaches and economic assessments to facilitate broader adoption. The findings underscore the potential role of biochar in enhancing forestry practices while calling for further studies to resolve uncertainties and improve its practical implementation. Graphical Abstract